Pengaruh Inovasi dan Orientasi Kewirausahaan Terhadap Keunggulan Bersaing UMKM Kuliner Pasar Lama Tangerang - Bilqis Alifia Adzani; Erwindi Saputra (Nawasena: Jurnal Ilmiah Pariwisata, 2022)
The city of Tangerang is currently developing its existing potential as a tourist attraction, which is part of the government's goals. One of them is the old culinary tourism market, which has the potential to be developed. And in 2012, the old market developed into a center for culinary tourism. This study explores issues related to the impact of innovation and collaboration on the competitive advantage of micro, small, and medium enterprises (MSMEs) in the old market of South Tangerang - Banten. The results of the study show that creative product innovation, market orientation, and marketing strategies have a positive impact on marketing performance. In addition, business development is also proven to affect marketing performance.